2010
DOI: 10.1590/s1678-77572010000600016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with paracetamol, ketorolac or etoricoxib did not hinder alveolar bone healing: a histometric study in rats

Abstract: Prostaglandins control osteoblastic and osteoclastic function under physiological or pathological conditions and are important modulators of the bone healing process. The non-steroidal anti-inflammatory drugs (NSAIDs) inhibit cyclooxygenase (COX) activity and consequently prostaglandins synthesis. Experimental and clinical evidence has indicated a risk for reparative bone formation related to the use of non-selective (COX-1 and COX-2) and COX-2 selective NSAIDs. Ketorolac is a non-selective NSAID which, at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…13,29,32 From these previous studies, we believe our dose would have the appropriate capability to prevent callus formation and subsequent fracture healing, if the effect exists in this population.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…13,29,32 From these previous studies, we believe our dose would have the appropriate capability to prevent callus formation and subsequent fracture healing, if the effect exists in this population.…”
Section: Methodsmentioning
confidence: 92%
“…In adult rat and rabbit studies, ketorolac administration has been shown to delay bone healing in some studies 13,14,22,27 but not in others. 29,32,33 In adult clinical studies, both Glassman et al 34 and Park et al 36 demonstrated increased nonunion rates in patients undergoing posterior spinal fusion who used ketorolac postoperatively. But Pradhan et al 37 failed to demonstrate any difference.…”
Section: Discussionmentioning
confidence: 99%
“…Although COX2 inhibitors are safer, their possible effects on delay in bone reunion and non-union required study. Various reports on drug dose-dependent effects on bone health have appeared, although in the present study, we did not administer different doses of NSAIDs [18][19][20]. The COX-selectivity of an NSAID governs the efficacy of analgesia as well as bone health.…”
mentioning
confidence: 85%
“…Tyl–The animals in this lot received Tylenol 40mg/ml/kg [24] (Paracetamol, Janssen-Cilag Pharmaceuticals Ltda, São Paulo, SP, Brazil). A 500 mg tablet of the drug Paracetamol was diluted in 100 ml of distilled water and administered orally [24]. This solution was given 30 min before the start of the bleaching treatment, then once every 12 h until euthanasia (Table 1).…”
Section: Methodsmentioning
confidence: 99%